Fourth Five-Year Plan (1969-74) - Planning Commission, Government of India (Planning Commission, Government of India, 1969)
State Plan—Head of Development, Outlay and Progress Centrally Sponsored Schemes- Heads of Development, Out-Lay and Progress, State Plan—Scheme-Wise Outlay and Progress Agricultural Programmes, Community Development and Co-operation, Irrigation and Power, Industry and Mining, Transport and Communication, Social Services, Miscellaneous, Centrally Sponsored Schemes—Scheme Wise Outlay and Progress Agricultural Programmes.
Planning Commission Government of India
Planning Commission, Government of India
Keywords: Fourth Five-Year Plan- India; Agricultural Production; Economic Development